2019
DOI: 10.1111/bjd.18619
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of quality‐of‐life measures in patients with peripheral vascular malformations: the OVAMA project

Abstract: Summary Background The OVAMA (Outcome Measures for Vascular Malformations) project determined quality of life (QoL) as a core outcome domain for patients with vascular malformations. In order to measure how current therapeutic strategies alter QoL in these patients, a patient‐reported outcome measurement (PROM) responsive to changes in QoL is required. Objectives To assess the responsiveness of two widely used generic QoL PROMs, the Medical Outcomes Study Short Form 36 (SF‐36) and Skindex‐29, in adult patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…A study on responsiveness of two generic QoL measures in adult patients with vascular malformations also found insufficient responsiveness, plausibly caused by large measurement errors. 20 A systematic review on outcome measurement instruments in vascular malformations found no other studies on responsiveness in this patient group or similar groups. 21 …”
Section: Discussionmentioning
confidence: 87%
“…A study on responsiveness of two generic QoL measures in adult patients with vascular malformations also found insufficient responsiveness, plausibly caused by large measurement errors. 20 A systematic review on outcome measurement instruments in vascular malformations found no other studies on responsiveness in this patient group or similar groups. 21 …”
Section: Discussionmentioning
confidence: 87%
“…“Radiological characteristics” are also not included in CDS because imaging follow‐up is not mandatory, but it should be reported if the examination was performed. In addition, although the OVAMA Steering Group has conducted studies to explore how to measure these core domains, there is no final core outcome measurement set 82–85 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, although the OVAMA Steering Group has conducted studies to explore how to measure these core domains, there is no final core outcome measurement set. [82][83][84][85] After evaluating treatment outcomes, follow-up is necessary for patients who no longer need special intervention. 7,8,11,24 When conditions permit, both clinical and imaging follow-up should be used because imaging can detect lesion changes more accurately and earlier than clinical follow-up.…”
Section: Post-treatment Managementmentioning
confidence: 99%
“…Non‐condition‐specific domains are advised to be measured by non‐condition‐specific outcome measurement instruments 11 . However, broadly used instruments such as the Short Form‐36 and Skindex‐29 seem to fall short for detecting changes in outcomes over time in this specific patient population 12 . Newer instruments such as the Patient‐Reported Outcomes Measurement Information System (PROMIS) 13 item banks may be used in this patient population as they are more likely to adequately capture small differences in the domains falling under quality of life 14,15 .…”
Section: Figurementioning
confidence: 99%
“… 11 However, broadly used instruments such as the Short Form‐36 and Skindex‐29 seem to fall short for detecting changes in outcomes over time in this specific patient population. 12 Newer instruments such as the Patient‐Reported Outcomes Measurement Information System (PROMIS) 13 item banks may be used in this patient population as they are more likely to adequately capture small differences in the domains falling under quality of life. 14 , 15 To fully capture those domains, the following PROMIS scales were identified: ‘pain interference’, ‘physical functioning’, ‘anxiety’, ‘depression’ and ‘social participation’.…”
mentioning
confidence: 99%